2018
DOI: 10.12973/eu-jer.7.3.583
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Resilience and Constant Hope in Students Studying Sports Science

Abstract: Individuals face negative events throughout their lives and such events can cause problems in every aspect of life. A high level of resilience is required to cope with such negative events. There are various factors that affect resilience. Hope is one of those factors. This factor provides a strong structure to individuals and keeps identified objectives alive. Based on this view, the aim of this study was to investigate the relationship between resilience and constant hope of students studying in a sports sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…This process explains the relationship between SFT skill and hope. Also, in other studies, a significant relationship was detected between hope and problem-solving skills (34) and psychological resilience (29), as well as between SFT and empathy ( 14) and happiness (33).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This process explains the relationship between SFT skill and hope. Also, in other studies, a significant relationship was detected between hope and problem-solving skills (34) and psychological resilience (29), as well as between SFT and empathy ( 14) and happiness (33).…”
Section: Discussionmentioning
confidence: 67%
“…Similar to the result of this study, it was found that in Turkey, nursing students in the study by Bilgiç et al (15) before the pandemic and university students in the study by Duman et al (16) had high levels of hope. In addition, the hope levels of sports science students before the pandemic were found to be moderate (29). In Turkey, there is a summer internship in the curriculum of midwifery departments.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, positive randomness assumption may also lead to think of having high level of hope. Similarly, Tolga et al (2018) found that resilience is related to constant hope, positively and moderately. As resilience increases, the level of constant hope is constantly increasing at the middle level.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, high and low hope is influenced by social support (Bareket-Bojmel et al, 2021). Meanwhile, hope is also known to contribute to resilience (Togo et al, 2018;Karaman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%